An R package for reading EPANET files. (October 2016) - Eck, Bradley J.
Abstract: The EPANET software for modeling piping networks is widely used for the design and analysis of water systems. This short communication describes epanetReader, an R package for reading EPANET files. The package reads network and simulation data in text-based file formats into R and provides summary and plotting functionality. epanetReader also introduces sparklines as a visualization of water network simulations. The package is available through the Comprehensive R Archive Network andGitHub.com . Highlights: The paper documents an R package for water network data. Files from the EPANET and EPANET-MSX simulators are supported. Package functions visualize data as maps and sparklines.